2016
DOI: 10.1039/c6an00375c
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative real-time detection of carcinoembryonic antigen (CEA) from pancreatic cyst fluid using 3-D surface molecular imprinting

Abstract: In this study, a sensitive, yet robust, biosensing system with real-time electrochemical readout was developed. The biosensor system was applied to the detection of carcinoembryonic antigen (CEA), which is a common marker for many cancers such as pancreatic, breast, and colon cancer. Real time detection of CEA during a medical procedure can be used to make critical decisions regarding further surgical intervention. CEA was templated on gold surface (RMS roughness ∼3-4 nm) coated with a hydrophilic self-assembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 25 publications
0
41
0
Order By: Relevance
“…The results showed that the immunoassay of 2-ring and 3-ring PAHs, naphthalene and anthracene, had a very small cross reaction (<1%). The four-ring compounds, pyrene, ben[a]anthracene and chrysene, had moderate cross-reactivity (15,22 and 31% for pyrene, ben[a]anthracene and chrysene, respectively). However, the benzo[b]uoranthene, which possessed ve rings like BaP, had a very high cross-reactivity of 61%.…”
Section: Cross-reactivity Of Other Pahsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the immunoassay of 2-ring and 3-ring PAHs, naphthalene and anthracene, had a very small cross reaction (<1%). The four-ring compounds, pyrene, ben[a]anthracene and chrysene, had moderate cross-reactivity (15,22 and 31% for pyrene, ben[a]anthracene and chrysene, respectively). However, the benzo[b]uoranthene, which possessed ve rings like BaP, had a very high cross-reactivity of 61%.…”
Section: Cross-reactivity Of Other Pahsmentioning
confidence: 99%
“…In addition, targeting BaP as a method of analysis also includes the application of a series of monoclonal antibodies generated by BaP derivatives, [9][10][11] and then a variety of immunochemical detection methods were developed for rapid detection of PAHs, such as enzyme-linked immunosorbent assay (ELISA), molecular imprinting biosensors, surface Plasma resonance immunosensors, uorescent immunoassays and electrochemical immunoassays. [12][13][14][15][16] Among these methods, uorescent immunoassay has become a promising method due to the recent development of new uorescent labeling techniques such as quantum dots, carbon nanotubes, and DNA labels, which have been used to improve the stability and sensitivity. [17][18][19] Among these new uorescence labeling techniques, uorescence immunoassays employing antibody-DNA/ dye immune complexes make uorescence amplication possible and more compatible with protein chips and lateral ow immunoassays.…”
Section: Introductionmentioning
confidence: 99%
“…The recognition element is responsible for selective binding of the target analytes, and the transducer produces the signal in accordance with the binding amount of the target analyte. The signal transition principle of the transducer can be based on the mass [1], optical [2,3], sound [4][5][6], fluorescence [7][8][9], electrochemical [10][11][12][13][14][15][16][17][18][19][20][21][22][23], or thermal response [24]. The recognition elements are usually biological agents which can be enzymes [25][26][27], antibodies [28][29][30], DNA [26,28,31,32], microbes [33][34][35][36][37][38][39][40][41], plant or animal cells [25,42,43], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al fabricated a potentiometric immunosensor for the detection of a cardiac biomarker-Troponin I-T-C with PANI/ DNNSA as a transducing layer. Different from traditional potentiometric sensors based on potentiometric response from analyte binding [333,334], this sensor depends on enzymatic redox reaction catalyzed on the sensing surface. It has a significantly low limit of detection (5 pg mL −1 or 56 fmol L −1 ) and a wide dynamic range (6 orders of magnitudes), making it an ideal substitute for conventional immunoassays currently used in clinical settings [335].…”
Section: Other Biomolecules Sensorsmentioning
confidence: 99%